MODERN APPROACHES TO THE CONTROL OF ACTIVE COMPONENTS OF CHOLERA CHEMICAL VACCINE - A. V. Gaeva; O. V. Gromova; O. S. Durakov; S. V. Generalov; O. A. Volokh (Разработка и регистрация лекарственных средств)
The paper considers the requirements to the production of pharmaceutical substances and the current trends in the toxicity assessment of the preparations obtained. The results of research of the use cell cultures for test bioactive substances, including cholera toxin are given. Evaluated are the advantages of in vitro methods application, in particular, continuous cell lines at some stages of cholera chemical vaccine manufacturing.